The Role of Indian Academic Libraries in Advancing and Achieving Sustainable Development Goals (LIS TODAY, 2024)
This study aims at defining the role of academic libraries in supporting the  sustainable development goals in the global quest as the United Nations calls for.  Academic libraries play important roles in supporting SDGs – particularly Quality  Education (Goal 4), Gender Equality (Goal 5), Reducing Inequalities (Goal 10),  and Strengthening the Means of Implementation, Partnerships (Goal 17). To this  end, this paper seeks to discuss how academic libraries in India can function as  a service provider in the achievement of these goals through assimilating their  services, collections, and policies into the IDAG. The research explores how  these libraries support educational justice, enable the disenfranchised, establish  gender parity, and build cooperation through openness and the use of digital tools.  However, critical roles notwithstanding, challenges that academic libraries face in  India include limited funding sources, digital resource constraints, professional  development opportunities, and low levels of networking both nationally and  internationally. Additionally, a general lack of understanding of what the libraries  can and should do with reference to the promotion of the SDGs limits potential.  Besides, the paper also discusses the current research findings regarding the  contributions of Indian academic libraries towards sustainable development  and adds the strategies for future enhancement for achieving the sustainable  development goals by 2030.
Keywords: Sustainable Development Goals; Academic Libraries; Digital Infrastructure; Lifelong Learning; Library Policies; Gender Equality; Global Collaboration.